Penyebab Lemahnya Budaya Membaca di Kalangan Siswa Sekolah Dasar pada Kurikulum Merdeka karena Bergantung dengan Aplikasi Chat GPT - Deli Puspita Anjami; Diandra Nofita; Adrias Adrias; Fadila Suciana (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study analyzes the factors contributing to the low interest in reading among elementary school students in the implementation of the Merdeka Curriculum, with a particular focus on the dependence on artificial intelligence applications such as ChatGPT. Technological advancements have made information access easier, but they have also raised concerns about the decline in the interest in deep book reading. Students who frequently use ChatGPT tend to only read summaries without delving deeper into the material, which weakens their critical thinking skills. In the Merdeka Curriculum, strong literacy is crucial, and therefore, the role of teachers and parents is essential to guide students in making books their primary learning resource. This research not only examines this phenomenon but also offers solutions for teachers and parents to enhance students' reading interest.